Standardised sampling of odonates (Odonata) in Serra da Estrela (Portugal) - 2013 and 2014 - Boieiro, Mário (2022)
Mountain ecosystems are crucial for biodiversity conservation since they host high biodiversity. This study reports novel information on odonate species diversity, distribution and abundance from Serra da Estrela Natural Park (Portugal). Twenty six odonate species were sampled in this protected area, including the first finding of Macromia splendens (Pictet, 1843). New populations of Oxygastra curtisii (Dale, 1834), a protected species under the Habitats Directive, was found in this Natural Park and novel distribution and ecological data was collected for most species, including several rare species (e.g., Aeshna juncea (Linnaeus, 1758), Sympetrum flaveolum (Linnaeus, 1758)). All data were collected using standardised sampling allowing its use as baseline for long-term monitoring of Serra da Estrela mountain biodiversity.